Applying Delphi method to develop sustainable city indexes: A case study of Chiang Mai, Thailand - Pongruengkiat, Wiwat; Tippayawong, Korrakot Y.; Aggarangsi, Pruk; Pichayapan, Preda; Katongtung, Tossapon; Tippayawong, Nakorn (TeMA - Journal of Land Use, Mobility and Environment, 2023)
Cities around the world have expanded and consumed many resources. The expansion of these cities has had a huge impact on our planet. There are many ideas about sustainable urban development around the world to slow down or stop the destruction of the environment. Sustainable urban development is a concept that allows the economy, society, and environment to grow together in a balanced and sustainable manner. Chiang Mai in Thailand is considered a city with much potential. It currently has good city planning. However, indicators to evaluate the potential of sustainable cities are still lacking. Hence, this work aims to develop appropriate indicators for assessing the sustainability of Chiang Mai city using the Delphi method of panel surveys. At least 20 experts in various fields were selected to take the Delphi surveys conducted in three rounds. The results of the Delphi processes showed that there were 35 indicators suitable for assessing Chiang Mai's potential as a sustainable city and helping with the development planning of Chiang Mai in the future.